IN - PROSESMETING 'n Nuwe Konsep In Vervaardigingstegnologie - Brink, p. (The South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: In-process measuring contributes towards automation in the manufacturing process and can also play an important role in quality by measuring characteristics during production. To enable one to effectively implement and utilize in-process measuring on a specific machine tool, it